Method for inhibiting side reactions of lead anodes, method for solid phase electrolysis of lead paste and electrolyte

CN116497403BActive Publication Date: 2026-10-27赵坤
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310235379.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-13
Publication Date
2026-10-27
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

[0005]本发明的目的是解决现有技术中存在的化学药剂消耗量较高,产生较多化学废品导致增加环境污染,同时,多种化学试剂的相互关系难以确定,从而难以找到适合的配比增加铅回收难度的不足之处,而提供一种抑制铅阳极副反应的方法、铅膏固相电解方法及电解液

Benefits of technology

[0026]1.本发明通过在铅膏固相电解铅的电解液中添加芦荟素,使得铅阳极的副反应基本得到抑制,铅阳极的副反应产物PbO2产量基本为0,固相电解铅的电流效率可以达到86%以上;同时通过使用特定浓度的芦荟素,对阳极副反应具有较好的抑制效果。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to waste lead-acid battery recycling, in particular to a method for inhibiting lead anode side reaction, a lead paste solid phase electrolysis method and an electrolyte, to solve the problems of high chemical reagent consumption, more chemical waste, environmental pollution, and the difficulty in determining the relationship between various chemical reagents, which increases the difficulty of lead recovery. The method for inhibiting lead anode side reaction adds aloe vera to the electrolyte of lead paste solid phase electrolysis, the electrolyte is a mixed solution of sulfuric acid and ammonium sulfate or a mixed solution of sulfuric acid and sodium sulfate or a sodium carbonate solution, aloe vera and lead ions first react on the anode surface to form a complex, which adheres to the anode surface, so that the side reaction of the lead anode is basically inhibited, and the current efficiency of solid phase electrolysis lead can reach more than 86%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the recycling of waste lead-acid batteries, specifically to methods for suppressing side reactions at the lead anode, solid-phase electrolysis of lead paste, and electrolyte. Background Technology

[0002] Solid-phase electrolysis is widely used in the waste lead-acid battery recycling industry. Lead paste is commonly used for solid-phase electrolysis of lead for lead recovery. However, side reactions often occur at the anode during solid-phase electrolysis, as shown in the following reaction equations:

[0003] Pb 2+ +H₂O + 2e = PbO₂ + 2H₂ +

[0004] Anodic side reactions reduce the current efficiency of electrolysis, and methods for suppressing anodic side reactions in solid-phase lead electrolysis are rarely reported. Publication CN113046787A discloses suppressing side reactions by adjusting the electrolyte composition or ratio. However, this method increases the consumption of chemical reagents, generates more chemical waste, and increases environmental pollution. Furthermore, the interactions between various chemical reagents are difficult to determine, making it difficult to find suitable ratios and increasing the difficulty of lead recovery. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies, such as high consumption of chemical reagents, generation of a large amount of chemical waste leading to increased environmental pollution, and difficulty in determining the interrelationships of various chemical reagents, which makes it difficult to find a suitable ratio and increases the difficulty of lead recovery. The invention provides a method for suppressing lead anode side reactions, a lead paste solid-phase electrolysis method, and an electrolyte.

[0006] To achieve the above objectives, the technical solution provided by this invention is as follows:

[0007] A method for suppressing lead anode side reactions is characterized by adding aloe vera to a lead paste solid-phase electrolyte; the electrolyte is a mixed solution of sulfuric acid and ammonium sulfate, a mixed solution of sulfuric acid and sodium sulfate, or a sodium carbonate solution.

[0008] Furthermore, the content of aloin in the electrolyte is 0.5-5 g / L.

[0009] Furthermore, the concentration of sulfuric acid in the mixed solution of sulfuric acid and ammonium sulfate is 0.5-15 g / L, and the concentration of ammonium sulfate is 1-2 mol / L.

[0010] Furthermore, the concentration of sulfuric acid in the mixed solution of sulfuric acid and sodium sulfate is 0.5-15 g / L, and the concentration of sodium sulfate is 1-2 mol / L.

[0011] Furthermore, the concentration of sodium carbonate in the electrolyte is 1-2 mol / L.

[0012] Meanwhile, a solid-phase electrolysis method for lead paste is also provided, which uses the above-mentioned method for suppressing the side reaction of lead anode, and its special feature is that it includes the following steps:

[0013] S1. Apply lead paste to the inside of the cathode frame to serve as the cathode for solid-phase electrolysis, and configure a pure lead anode plate as the anode;

[0014] S2. Prepare an electrolyte and add it to an electrolytic cell, and add aloe vera extract to the electrolytic cell; the electrolyte is a mixed solution of sulfuric acid and ammonium sulfate, or a mixed solution of sulfuric acid and sodium sulfate, or a sodium carbonate solution;

[0015] S3. Place the cathode and anode described in step S1 into the electrolytic cell described in step S2, connect the electrolytic circuit, turn on the power supply, and apply DC power to the cathode and anode.

[0016] S4. Perform an electrolytic reaction to reduce the lead paste to obtain electrolytic lead.

[0017] Furthermore, in step S1, there are a total of 2 anodes;

[0018] In step S3, the distance between the two anodes is 100mm;

[0019] In step S4, the electrolysis reaction is carried out in constant current mode, and the current density in the electrolysis reaction is 73.5-134 A / m. 2 The electrolysis time is 40-72 hours.

[0020] Meanwhile, the present invention also provides an electrolyte for suppressing lead anode side reactions, which is characterized in that it comprises a mixed solution of sulfuric acid, ammonium sulfate and aloin, or a mixed solution of sulfuric acid, sodium sulfate and aloin, or a mixed solution of sodium carbonate and aloin.

[0021] Furthermore, in the mixed solution of sulfuric acid, ammonium sulfate, and aloin, the concentration of sulfuric acid is 0.5-15 g / L, the concentration of ammonium sulfate is 1-2 mol / L, and the concentration of aloin is 0.5-5 g / L.

[0022] The concentration of sulfuric acid in the mixed solution of sulfuric acid, sodium sulfate, and aloin is 0.5-15 g / L, the concentration of sodium sulfate is 1-2 mol / L, and the concentration of aloin is 0.5-5 g / L.

[0023] The concentration of sodium carbonate in the mixed solution of sodium carbonate and aloin is 1-2 mol / L, and the concentration of aloin is 0.5-5 g / L.

[0024] Aloe vera is used to react with lead ions on the anode surface to form a complex that adheres to the anode surface, inhibiting the side reactions of lead ions on the anode. When the concentration of aloe vera is low, the side reactions on the anode are large and the current efficiency is low, while when the concentration of aloe vera is high, the viscosity of the electrolyte increases and the current efficiency is low.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. This invention, by adding aloin to the electrolyte of solid-phase lead electrolysis using lead paste, effectively suppresses the side reactions at the lead anode, resulting in a near-zero yield of PbO2, a byproduct of the lead anode side reaction, and achieving a current efficiency of over 86% for solid-phase lead electrolysis. Furthermore, the use of aloin at a specific concentration effectively inhibits anode side reactions.

[0027] 2. The aloin in this invention is a plant-based product that does not pollute the environment and reduces the amount of chemical components in the electrolyte. Detailed Implementation

[0028] The present invention will be further described in detail below with reference to specific embodiments:

[0029] The method for suppressing the anode side reaction in lead paste solid-phase electrolysis of lead of the present invention is specifically applied in the process of lead paste solid-phase electrolysis of lead. By adding aloe vera to the electrolyte, the anode side reaction is suppressed, the current efficiency in lead electrolysis is improved, the side reaction products are reduced, and the lead recovery rate is increased.

[0030] The following experimental data on solid-phase electrolysis of lead paste demonstrates the effectiveness of aloin in inhibiting anodic side reactions.

[0031] Experiment 1

[0032] S1. Apply 1556g of lead paste (10% moisture content) to a stainless steel cathode frame. The cathode frame dimensions are 200*200*10mm (width*height*thickness), with an effective cathode area of ​​0.07m². 2 The cathode frame of the above-mentioned coated plate is used as the cathode for solid-phase electrolysis. Two pure lead anode plates are configured, with the width*height*thickness dimensions of the anode plates being 200*200*3mm (including the crossbeam), and the total weight of the two anode plates is 2916.8g.

[0033] The lead phase composition of lead paste is as follows:

[0034] 77.35% 31.58% 10.32% 21.77% 13.68%

[0035] S2. Prepare 6L of electrolyte solution with a sulfuric acid concentration of 14g / L and an ammonium sulfate concentration of 1mol / L and place it in the electrolytic cell;

[0036] S3. Add 6g of aloin to the electrolytic cell, with an aloin concentration of 1g / L.

[0037] S4. Place the above-mentioned 1 cathode and 2 anodes in the above-mentioned electrolytic cell, keeping the distance between the same electrodes of the electrolytic anodes 100mm; connect the electrolytic circuit, turn on the power supply, and apply DC power to the cathode and anode.

[0038] S5. Adopt constant current mode, controlling the current density to 105 A / m. 2 Electrolysis was performed for 48 hours to reduce the coated lead paste to electrolytic lead. 1322.08 g of electrolytic lead was weighed, with a moisture content of 16.36%. The two anode pieces weighed a total of 2917.3 g. The phase composition of the electrolytic lead was analyzed and is shown in the table below.

[0039] 96.25% 0.35% 2.13% 0 93.77%

[0040] S6. Calculate the test technical indicators

[0041] Current efficiency = 309.894 / 352.8 = 87.84%;

[0042] Anode weight gain rate = (2917.3 - 2916.8) / 2916.8 = 0.017%.

[0043] Experiment 2

[0044] S1. Apply 1487g of lead paste (with a moisture content of 9%) to a stainless steel cathode frame. The cathode frame dimensions are 200*200*10mm (width*height*thickness), and the effective cathode area is 0.07m². 2 The cathode frame of the above-mentioned coated plate is used as the cathode for solid-phase electrolysis. Two pure lead anode plates are configured, with the width*height*thickness dimensions of the anode plates being 200*200*3mm (including the crossbeam), and the total weight of the two anode plates is 2917.2g.

[0045] The lead phase composition of lead paste is as follows:

[0046] 76.71% 29.29% 11.42% 25.33% 10.67%

[0047] S2. Prepare 6L of electrolyte solution with a sulfuric acid concentration of 3g / L and a sodium sulfate concentration of 1.8mol / L and place it in the electrolytic cell;

[0048] S3. Add 12g of aloin to the electrolytic cell, with an aloin concentration of 2g / L.

[0049] S4. Place the above-mentioned 1 cathode and 2 anodes in the above-mentioned electrolytic cell, keeping the anode spacing 100mm; connect the electrolytic circuit, turn on the power supply, and apply DC power to the cathode and anode.

[0050] S5. Constant current mode is adopted, and the current density is controlled at 73.5A / m.2 Electrolysis was performed for 72 hours to reduce the coated lead paste to electrolytic lead. 1257.41 g of electrolytic lead was weighed, with a moisture content of 14.59%. Two anode pieces weighed 2917.4 g. The phase composition of the electrolytic lead was analyzed and is shown in the table below:

[0051] 95.71% 0.52% 1.64% 0 93.55%

[0052] S6. Calculate the test technical indicators

[0053] Current efficiency = 320.225 / 370.44 = 86.45%;

[0054] Anode weight gain rate = (2917.4 - 2917.2) / 2917.2 = 0.007%.

[0055] Experiment 3

[0056] S1. Apply 1507g of lead paste (8% moisture content) to a stainless steel cathode frame. The cathode frame dimensions are 200*200*10mm (width*height*thickness), and the effective cathode area is 0.07m². 2 The cathode frame of the above-mentioned coated plate is used as the cathode for solid-phase electrolysis. Two pure lead anode plates are configured, with the width*height*thickness dimensions of the anode plates being 200*200*3mm (including the crossbeam), and the total weight of the two anode plates is 2917.5g.

[0057] The lead phase composition of lead paste is as follows:

[0058] 74.82% 35.73% 11.94% 19.61% 7.54%

[0059] S2. Prepare 6L of electrolyte with a sodium carbonate concentration of 1.5mol / L and place it in the electrolytic cell;

[0060] S3. Add 18g of aloin to the electrolytic cell, with an aloin concentration of 3g / L.

[0061] S4. Place the above-mentioned 1 cathode and 2 anodes in the above-mentioned electrolytic cell, keeping the anode spacing 100mm; connect the electrolytic circuit, turn on the power supply, and apply DC power to the cathode and anode.

[0062] 5. Constant current mode is adopted, and the current density is controlled at 134A / m. 2 Electrolysis was performed for 40 hours to reduce the coated lead paste to electrolytic lead. 1276.33 g of electrolytic lead was weighed, with a moisture content of 17.45%. The two anode pieces weighed a total of 2917.9 g. The phase composition of the electrolytic lead was analyzed and is shown in the table below.

[0063] 95.85% 0.42% 1.87% 0 93.56%

[0064] S6. Calculate the test technical indicators

[0065] Current efficiency = 324.258 / 375.2 = 86.42%;

[0066] Anode weight gain rate = (2917.9 - 2917.5) / 2917.5 = 0.014%.

[0067] Based on the results of the three experiments, the corresponding technical indicators were calculated. It can be seen that the use of aloin suppressed the anode side reaction. The anode weight gain rates in the three experiments were 0.017%, 0.007%, and 0.014%, respectively. The weight gain rate was very small, which met the expected effect and showed a good inhibitory effect on the anode side reaction. In the solid-phase electrolysis of lead paste, the lead ion content is about 5-200 mg / L. During the electrolysis process, aloin reacts with lead ions on the anode surface first to form a complex. The complex adheres to the anode surface, thereby inhibiting the side reaction of lead ions at the anode.

[0068] The electrolyte for lead paste solid-phase electrolysis is a mixed solution of sulfuric acid and ammonium sulfate, or a mixed solution of sulfuric acid and sodium sulfate, or a sodium carbonate solution. In the mixed solution of sulfuric acid and ammonium sulfate, the concentration of sulfuric acid is 0.5-15 g / L, and the concentration of ammonium sulfate is 1-2 mol / L. In the mixed solution of sulfuric acid and sodium sulfate, the concentration of sulfuric acid is 0.5-15 g / L, and the concentration of sodium sulfate is 1-2 mol / L. In the sodium carbonate solution, the concentration of sodium carbonate is 1-2 mol / L. The electrolyte used to suppress lead anode side reactions is prepared by adding aloe vera extract to the electrolyte of the above-mentioned lead paste solid-phase electrolysis. The preferred concentration of aloe vera extract is 0.5-5 g / L. Within this concentration range, the reaction rate is faster, and the suppression effect on anode side reactions is better. When the concentration of aloe vera extract is low, the anode side reactions are larger, and the current efficiency is lower. Conversely, when the concentration of aloe vera extract is higher, the electrolyte viscosity increases, and the current efficiency is lower.

Claims

1. A method for suppressing lead anode side reactions, characterized in that: Aloe vera is added to the lead paste solid electrolyte. The aloe vera reacts with lead ions to form a complex, thereby inhibiting the side reactions of lead ions at the anode. The electrolyte is a mixed solution of sulfuric acid and ammonium sulfate, or a mixed solution of sulfuric acid and sodium sulfate, or a sodium carbonate solution; The electrolyte contains 0.5-5 g / L of aloin.

2. The method for suppressing lead anode side reactions according to claim 1, characterized in that: The concentration of sulfuric acid in the mixed solution of sulfuric acid and ammonium sulfate is 0.5-15 g / L, and the concentration of ammonium sulfate is 1-2 mol / L.

3. The method for suppressing lead anode side reactions according to claim 1, characterized in that: The concentration of sulfuric acid in the mixed solution of sulfuric acid and sodium sulfate is 0.5-15 g / L, and the concentration of sodium sulfate is 1-2 mol / L.

4. The method for suppressing lead anode side reactions according to claim 1, characterized in that: The concentration of sodium carbonate in the electrolyte is 1-2 mol / L.

5. A solid-phase electrolysis method for lead paste, using the method for suppressing lead anode side reactions as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Apply lead paste to the inside of the cathode frame to serve as the cathode for solid-phase electrolysis, and configure a pure lead anode plate as the anode; S2. Prepare an electrolyte and add it to an electrolytic cell, and add aloe vera extract to the electrolytic cell; the electrolyte is a mixed solution of sulfuric acid and ammonium sulfate, or a mixed solution of sulfuric acid and sodium sulfate, or a sodium carbonate solution; S3. Place the cathode and anode described in step S1 into the electrolytic cell described in step S2, connect the electrolytic circuit, turn on the power supply, and apply DC power to the cathode and anode. S4. Perform an electrolytic reaction to reduce the lead paste to obtain electrolytic lead.

6. The solid-phase electrolysis method for lead paste according to claim 5, characterized in that: In step S1, there are a total of 2 anodes; In step S3, the distance between the two anodes is 100mm; In step S4, the electrolysis reaction is carried out in constant current mode, and the current density in the electrolysis reaction is 73.5-134 A / m. 2 The electrolysis time is 40-72 hours.

7. An electrolyte for suppressing lead anode side reactions, characterized in that: The solution includes a mixed solution of sulfuric acid, ammonium sulfate and aloin, or a mixed solution of sulfuric acid, sodium sulfate and aloin, or a mixed solution of sodium carbonate and aloin, wherein the aloin is used to react with lead ions to form a complex and inhibit the side reaction of lead ions at the anode. The concentration of the aloin is 0.5-5 g / L.

8. The electrolyte for suppressing lead anode side reactions according to claim 7, characterized in that: The concentration of sulfuric acid in the mixed solution of sulfuric acid, ammonium sulfate and aloe vera is 0.5-15 g / L, and the concentration of ammonium sulfate is 1-2 mol / L. The concentration of sulfuric acid in the mixed solution of sulfuric acid, sodium sulfate and aloe vera is 0.5-15 g / L, and the concentration of sodium sulfate is 1-2 mol / L. The concentration of sodium carbonate in the mixed solution of sodium carbonate and aloe vera is 1-2 mol / L.

Citation Information

Patent Citations

  • Electrolyte, system and method for waste lead storage battery lead plaster ternary system wet-process lead recovery

    CN113046787A

  • Electrolyte and method for electrolyzing and refining crude lead

    CN104746098A

  • Method for recovering lead from waste lead paste by solid phase electrolysis method

    CN111455404A